Excessive use of mobile social networking sites: Negative consequences on individuals. (December 2016) - Zheng, Xiabing; Lee, Matthew K.O.
Abstract: While pervasive technologies, such as mobile social networking sites (SNS), can contribute to increased enjoyment and convenience, their pervasive nature can also result in excessive use and consequently may arise several negative outcomes. We applied cognitive behavioral model and social cognitive theory to explain the negative consequences related to family, personal and professional life of excessive use of mobile SNS. The research model was empirically tested with 490 mobile SNS users. Our findings significantly contribute to the domain of "dark side of information technology" by theoretically and empirically investigating the negative outcomes of excessive use, and further examining their inter-relationships. Highlights: We examined the negative outcomes of excessive use of mobile social networking sites. Three types of conflicts (viz. technology-family, technology-personal, and technology-work) were examined. Excessive use enhanced cognitive preoccupation. Excessive use and cognitive preoccupation were associated with the three types of conflicts. The relationships and the roles of these three conflicts on technostress were also examined.